IMPLEMENTASI FUNGSI MANAJEMEN SENI PERTUNJUKAN PADA KOMUNITAS SENI HITAM PUTIH PADANGPANJANG - saadudin; Firdaus (Unika Santu Paulus Ruteng, 2021)
This study aims to reveal how the management functions of the Padang Panjang Black and White Art Community. This research is evaluative research that tries to show descriptively in the form of a narrative about the facts based on the opinion of the perpetrator. Research data or information is collected through observation, interview, and documentation study. The collected data were then analyzed, namely, reducing data, displaying data, drawing (temporary) conclusions, verifying conclusions through triangulation techniques before making conclusions. The findings show that the Black and White Art Community organizationally still relies on someone who acts as a coordinator, the organizational structure has not placed on competence, the work displayed is still sporadic, not well organized following professional management functions planning, organizing, actuating, motivating, controlling, and evaluating.